Estetika Wayang - Hadiprayitno, Kasidi (LPPM Universitas PGRI Adi Buana Surabaya, 2014)
The basics are the puppet aesthetic perspective of the relation elements of beauty in the unity of the structure of the wayang. Understanding the true aesthetic beauty rests on the concept of thought that developed and followed by Western thinkers, however, in the operatate of implemeta- tion still refer to terms that are known in the art of traditional puppet convention. Not all data in the beauty of the puppets can be presented in this short article, but limited to the aspects of beauty essentials only such convention and modernity in the universe puppet, puppet or convention in the art of puppetry, in the currency of view of the puppet, and aesthetic concepts in art puppetry and puppetry.